PENGARUH PEMBERIAN EKSTRAK DAUN KELOR (Moringa oleifera L.) TERHADAP PROFIL FARMAKOKINETIKA PARASETAMOL SECARA ORAL PADA TIKUS JANTAN GALUR SPRAGUE-DAWLEY - Syifa Nur (2023)
Moringa leaves are widely utilized by the community, one of which is as a traditional medicine for analgesic and antipyretic purposes. Paracetamol is a conventional drug commonly used for self-medication and readily available over-the-counter as an analgesic and antipyretic. Traditional medicine and conventional drugs, when used together, can cause interactions. The aim of this research is to determine the pharmacokinetic profile of paracetamol when administered together with moringa leaves in rats. The research method employed was a true experimental design with a posttest only control group using male Sprague-Dawley rats, with 6 rats in each group. The control group received an oral dose of 9mg/200g body weight of paracetamol, while the treatment group received an oral dose of 9mg/200g body weight of paracetamol and 60mg/200g body weight of moringa leaf extract. Blood samples were taken from the lateral tail vein of the rats at 30, 60, 120, 180, and 240 minutes. The determination of paracetamol levels in plasma was analyzed using a UV-Vis spectrophotometer at a wavelength of 244 nm. The results of the study showed that the administration of moringa leaf extract decreased the pharmacokinetic profile of paracetamol in terms of elimination half-life (t½), AUC0-inf, Cmax, Tmax, and total AUC, while it increased Vd, Cl, AUC0-240, Ka, and Ke. However, the administration of moringa leaf extract did not significantly affect the pharmacokinetic profile of paracetamol based on the unpaired t-test statistical analysis (p>0.05).